Deglutição e qualidade de vida na síndrome pós-covid-19 - Pichini, Fernanda dos Santos (2023)
Introduction: In the current context, the new coronavirus, called SARS-CoV-2, presents itself as an acute infectious respiratory disease, with systemic repercussions, which characterize the Post-COVID-19 Syndrome. This situation may be present in 30% of patients who require hospitalization. Therefore, compromises in the swallowing process, such as safety and efficacy during swallowing and quality of life have been the focus of investigation. Objective: To investigate and relate aspects of swallowing and quality of life of individuals who were infected by COVID-19, stratified by disease severity and sex. Method: Cross-sectional, observational and descriptive study, which included adult individuals, of both sexes, after hospitalization due to COVID-19 in a University Hospital who were referred to the Post-COVID-19 Rehabilitation Outpatient Clinic of the aforementioned Hospital in the period of August and December 2021. All were evaluated from at least 30 days after the hospitalization period. Individuals who had laryngeal alteration, neurological impairment, severe orofacial pain, including trigeminal neuropathy prior to COVID-19 and lung disease not due to COVID-19 were excluded. Those eligible for the study underwent risk assessment for dysphagia using the Eating Assessment Tool-10 (EAT-10), clinical swallowing assessment using the Volume–Viscosity Swallowing Test (V-VST) and Risk Assessment for Dysphagia (PARD) protocols.) and the Short Form 36 Health Survey Questionnaire (SF-36). To complement the assessments, data regarding the length of hospital stay, ICU stay and ventilatory support were collected from the University Hospital Management Application (AGHU). Results: 39 adult individuals were included in the study, after hospitalization due to COVID-19, the mean age was 51.7(18.9) years. The sample was stratified into critical 14 (35.9%) and severe 25 (64.1%). The hospital stay of the total sample was 14 (3-60) days. When analyzing the risk of dysphagia, due to the severity of COVID-19, it can be observed that the critical group presented a risk for dysphagia in the EAT-10 questionnaire (21.4%); PARD (50%) and altered V-VST signs of efficacy (57.1%) and safety (21.4%), with statistical difference between genders, in the EAT-10, women had a higher risk of dysphagia than men (38.1%; p=0.04). In the severe group, the risk observed was in the EAT-10 (28%), PARD (24%) and efficacy and safety (65.2% and 21.7%), respectively, with no statistical differences between genders (p>0.05). As for quality of life (SF-36), a statistical difference was found in the critical group, women had worse quality of life in the domains of functional capacity (p=0.02); vitality (0.04); mental health (0.01) and general health (p=0.01). Conclusion: The risk for dysphagia was found in patients with postCOVID-19 syndrome, in both groups of patients, severe and critical. And, in more than a third of women, in the critical group, they were at risk for dysphagia. There was a significant difference in quality of life between genders in the critical group. Women had a greater impact on the domains of functional capacity, vitality, mental health and general health.